2020
DOI: 10.1140/epjc/s10052-020-8286-y
|View full text |Cite
|
Sign up to set email alerts
|

N spike D-strings in AdS Space with mixed flux

Abstract: We use Dirac-Born-Infeld action to study the spinning D-string in $$AdS_3 $$AdS3 background in the presence of both NS-NS and RR fluxes. We compute the scaling relation between the energy (E) and spin (S) in the ‘long string limit’. The energy of these spiky string is found to be a function of spin with the leading logarithmic behaviour and the scaling relation appears to be independent of the amount of flux present. We further discuss folded D-string solutions in $$AdS_3$$AdS3 background with pure NS-NS and R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The background solution has been shown to satisfy type IIB supergravity field equations, given the parameters are related by the constraint q 2 + q2 = 1, where q and q are associated to the field strength of NS-NS fluxes and RR fluxes respectively. There have been multiple studies on various classical string solutions in detail in [54][55][56][57][58][59][60][61][62]. We study class of rigidly rotating strings and speculate its corresponding dual states in gauge theory in the mixed flux background.…”
Section: Jhep11(2021)178mentioning
confidence: 99%
“…The background solution has been shown to satisfy type IIB supergravity field equations, given the parameters are related by the constraint q 2 + q2 = 1, where q and q are associated to the field strength of NS-NS fluxes and RR fluxes respectively. There have been multiple studies on various classical string solutions in detail in [54][55][56][57][58][59][60][61][62]. We study class of rigidly rotating strings and speculate its corresponding dual states in gauge theory in the mixed flux background.…”
Section: Jhep11(2021)178mentioning
confidence: 99%
“…In the scope of this extended gravity, Yadav et al [33] have proposed the existence of non-exotic compact star, that validates the energy conditions and stability of the model. Biswas et al [34] have studied the anisotropic spherically symmetric strange star and have shown the validity of the conditions used in the model. Maurya et al [35] have suggested an embedded approach to study the existence of compact structures that describes anisotropic matter distributions in the framework of matter geome-try coupling.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, we find the dispersion relation between various conserved charges of semi-classical string dynamics in AdS space, which in turn gives the anomalous dimensions of the dual boundary field theory operators [4][5][6][7][8][9]. In particular, the study of rigidly rotating string in the large charge limit moving in some curved background has gained much attention in establishing the AdS/CFT holographic realization [10][11][12][13][14][15][16][17][18]. In order to have a better grasp on the spectrum of AdS 5 × S 5 superstring theories, various other class of classical string solutions has also been studied to a great extent.…”
Section: Introductionmentioning
confidence: 99%